Safety Profile of Combined Same-Day Treatment for Botulinum Toxin With Full Face Nonablative Fractionated Laser Resurfacing. Issue 4 (April 2021) - Pomerantz, Hyemin; Akintilo, Lisa; Shaw, Katharina; Lederhandler, Margo; Anolik, Robert; Geronemus, Roy G.
Abstract : BACKGROUND: Spread of botulinum toxin outside the treated muscle is a concern, when energy-based device treatment is performed on the same day as toxin injection. OBJECTIVE: We assessed the frequency of eyelid ptosis after the glabella/periorbital botulinum toxin injection and nonablative fractionated laser performed at the same session. METHODS AND MATERIALS: This single-center, retrospective study identified treatments consisting of glabella and/or periorbital botulinum toxin injection and nonablative fractionated laser treatment to full face from 2017 to 2019 and eyelid ptosis determined by documentation of the complication at a follow-up encounter, or prescription of apraclonidine. RESULTS: Six hundred sixteen treatments of glabella/periorbital botulinum toxin injection and full-face nonablative fractionated laser on the same day on 393 individuals were identified. Five hundred eighty treatments (94%) included botulinum toxin injected in the glabella, 541 (88%) in the periorbital areas, and 508 (82%) in the forehead. Nonablative fractionated lasers used to treat the cohort were a 1, 927-nm thulium and a 1, 550-nm er:glass laser. Eyelid ptosis complication was documented in one case (0.2%) following the combined laser and toxin treatment. CONCLUSION: The risk of spread of glabella/periorbital botulinum toxin to an unintended muscle was minimal in the setting of the concomitant full-face nonablative fractionated laser.